P19 A mixed method study to evaluate the medicines optimisation pathway following virtual outpatient clinics. Issue 5 (20th April 2022) - Tsang, Victoria; Eftychiou, Linda; Vas, Venessa; Christiansen, Nanna; Crook, Joanne; Bentley, Sian; Makhecha, Sukeshi
Abstract : Aim: In March 2020, COVID-19 triggered an NHS directive to reduce face-to-face consultations and adapt to virtual clinics. 1 Hospital pharmacies, each with their own model of care, quickly innovated to ensure patients received their medication safely. The aim of this study was to evaluate the provision of medications optimisation for paediatric patients following virtual outpatient consultations (VOC) and explore potential improvements for future implementations. Method: This was a mixed method study using quantitative data; which reviewed medications sent to patients in red, amber, and green categories 2 and qualitative data; using patient feedback, to evaluate the processes in three London hospitals. Pathway mapping (PM) sessions, with multidisciplinary team involvement, were conducted across these hospitals to identify areas for improvement and analyse gaps in services. Virtual PM sessions were attended by 30 representatives across the multidisciplinary team including: pharmacists, nurses, consultants, pharmacy technicians, post room attendants; and general, operational, and project managers. Semi-structured questionnaires were used to conduct one to one telephone interviews with patients' families. A separate topic guide was used to interview General practitioners (GP) and primary care network (PCN) pharmacists. The audio recordings were transcribed as 'intelligent verbatim' and analysed using Nvivo. Braun and Clarke's six phases approach was used to conduct an inductive thematic analysis. 3 To improve the rigorousness of the study, more than 50% of the transcript were double coded. 4 As this was a service evaluation, ethics approval was not necessary. The project was registered with each hospital's clinical audit department. Results: The three process maps were analysed and potential improvements for the medicines optimisation pathway were assessed by a paediatric pharmacy subgroup using ease-impact matrix. Potential improvements include: exploration and use of Electronic Prescription Service by secondary and tertiary care, improving communication through Information Technology systems between prescribers and hospital pharmacists, and the creation of a transparent standard operating procedure regarding medication supply following VOC. Seventy-one patients' families across the sites were interviewed between January-May 2021 to reflect on their experience of receiving medications following a VOC. Four GPs and one PCN pharmacist were interviewed in May 2021 to assess on the impact of VOC on primary care. Key reflections from themes generated include the convenience of receiving medications from hospital pharmacies following VOC, satisfaction of the current process, including medicines packaging and medicines information provided to patients and their families. Other reflections included limitations of the current process and its implication on patient safety. Medicines information helplines and education provided by pharmacists were regarded by patients' families and GPs as a valuable attribute. Conclusion: Patients' families appreciated the current model of care, however patients' families and primary care healthcare professionals have identified both challenges and suggestions for improvement in delivering the current model. Future research should focus on a mixed mode of integrated care with green and amber medications 2 prescribed directly to community pharmacies with clinical screening and counselling conducted by hospital pharmacists. References: Stevens S and Pritchard A. Important and urgent – next steps on NHS response to Covid-19. NHS England [Online]. 17 March 2020: Available at: https://www.england.nhs.uk/coronavirus/wp-content/uploads/sites/52/2020/03/urgent-next-steps-on-nhs-response-to-covid-19-letter-simon-stevens.pdf Guy's and St Thomas' NHS Foundation Trust, Kings College Hospital NHS Foundation Trust, Lewisham and Greenwich NHS Trust. South East London Joint Medicines Formulary. netFormulary . [Online]. 2020: Available at: http://www.selondonjointmedicinesformulary.nhs.uk/ Braun V and Clarke V. Using thematic analysis in psychology. Qualitative Research in Psychology 2006;3 :77-101. Maher C, Hadfield M, Hutchings M, et al . Ensuring rigor in qualitative data analysis: a design research approach to coding combining NVivo with traditional material methods. International Journal of Qualitative Methods 2018;17 :1-13.